Reproducibility of a laboratory based 20-km time trial evaluation in competitive cyclists using the Velotron Pro ergometer - Sporer, B. C.; McKenzie, D. C. (International Journal of Sports Medicine, 2007)
The purpose of this study was to evaluate the reliability of a 20-km cycling time trial using the Velotron cycle ergometer in competitive cyclists. Twenty male cyclists (V·O2max = 68.5 ± 3.6 ml · kg-1 · min-1; peak power (Ppeak) = 469 ± 33 W) participated in this study. Each subject performed a V·O2max test and 3 separate 20-km time trials (TT1, TT2, and TT3). Data from trials were compared using a one-way ANOVA. Coefficients of variation (CV) and 95 % confidence intervals (CI) were calculated between trials. Values are mean ± SD unless otherwise noted. Performance time Ttot (30.03 ± 1.24, 30.12 ± 1.21, and 30.14 ± 1.21 min) and mean absolute power (Pmean) (326 ± 35, 323 ± 35, 322 ± 34 Watts) were not significantly different across TT1 - TT3. Pmean was highly related between TT1 - TT2 (r = 0.96; p < 0.01) and TT2 - TT3 (r = 0.97; p < 0.01). A low CV was also demonstrated between trials for Pmean (TT1 - TT2 = 2.1 %, CI = 1.6 % to 3.1 %; TT2 - TT3 = 1.9 %, CI = 1.4 % to 2.8 %). Ppeak and Pmean were both correlated to Ttot in TT1 with Pmean accounting for most of the variance in Ttot (R2 = 0.993). These data show that performance in a 20-km time trial using the Velotron ergometer is highly reproducible in competitive cyclists. Furthermore, the CV variance demonstrated between trials is comparable to that expected during actual performance in elite athletes.